PENGENALAN DAN PELATIHAN PEMROGRAMAN DASAR IOT DENGAN SIMULASI WOKWI BAGI SISWA TKJ SMKN NOEMUTI - Ngaga, Emerensiana; Siki, Yovinia Carmeneja Hoar; Manehat, Donatus Joseph; Bria, Yulianti Paula; Nani, Paskalis Andrianus (Jurnal Abdimas Bina Bangsa, 2024)
This program aims to apply science and technology through a community service program. The application of science and technology includes practical training in the basics of circuit making and programming through Wokwi simulations. This is done to improve knowledge and skills through practice for students and teachers of the Computer and Network Engineering Study Program at SMK N Noemuti. The activities carried out include introduction and training in basic IoT programming with Wokwi hardware simulations that are easy to understand and comprehend. The activity begins with an introduction to IoT, algorithms and programming, and the Wokwi platform; creating a Wokwi account and Basic IoT Programming training. To achieve the above goals, training and mentoring were carried out for 3 months. The methods used are lectures, practices, questions and answers, discussions and exercises. The results of this community service activity are able to provide solutions to the lack of knowledge of programming and developing IoT devices because there is no special learning about algorithms and programming. In addition, this community service activity also provides solutions to the unavailability of IoT hardware that supports learning activities. This is measured from the results of quantitative and descriptive evaluations which show an increase in student knowledge reaching 100% for quantitative evaluations and positive review results from descriptive evaluations.